Immature biology and morphology of an obligate myrmecophilous butterfly Catapaecilma major moltrechti (Wileman) (Lepidoptera: Lycaenidae) from Taiwa - Hsu, Yu-Feng; Huang, Chia-Lung; Huang, Hang-Chi (Zootaxa, 2016)
The immature biology and morphology of Catapaecilma major moltrechti (Wileman) from Taiwan are reported. The larva of this taxon is proven to be largely predacious on a few scale insect species attended by ant Crematogester rogenhoferi in satellite nests constructed by the ants, but it also consumes plant material within or near ants’ satellite nests in elder instars. The discovery of the food habit of this taxon is interesting as the larva of C. major is known to be phytophagous in India and Sri Lanka.